A Qualitative Study On The Decoupling Of Environmental And Social Issues From Management Control Systems In A Petroleum Company: An Institutionalist Approach - Abdalla, Yousif Abdelbagi (2013)
The main objective of this study is to understand and explain how environmental and social issues are considered and embraced in the management control system (MCS) of an oil and gas company located in Sudan. An interpretive case study is used whereby data are collected through semi-structured interviews with relevant individuals from inside and outside the company. Document reviews, informal conversations and observations are also employed to support the data generated from the interviews. The findings of this study are informed by the New Institutional Sociology theory, which emphasizes that MCS configurations are driven not only by economic or functional factors, but also by institutional factors. From the case findings, it would appear that the governmental laws and regulations, the pressure from and concerns of NGOs, the company’s goal to protect and maintain its reputation and public image, and the high expectations of local communities, are among the main factors that pushed the company to consider environmental and social issues in its operations.